Cairo's Halal Restaurant Industry: Exploring Sharia-Based Financing and Fatwa Influence - Mariam Elbanna; Muhammad Wael Chafoory; Sondos Jehad Shnewra (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the level of Sharia compliance in the financing practices of mudharabah contracts based on the fatwas of the Council of Egyptian Scholars, using the case study of a Sharia Restaurant in Egypt. This research is motivated by the importance of implementing Sharia principles in financial transactions, particularly in the microeconomic sector, to align with the values of justice and transparency as taught in Islam. Theoretical framework: The theoretical framework of this study refers to the concept of Sharia compliance and the fundamental principles of fiqh muamalat, particularly in syirkah and mudharabah contracts, as well as contemporary perspectives on fatwas as a source of Islamic economic law. Literature review: The literature review includes previous studies on the implementation of mudharabah contracts in the microeconomic sector and emphasizes the importance of supervision by local scholars in economic practices. Methods: This study employs a qualitative approach using in-depth interviews, participatory observation, and documentation to thoroughly explore the financing practices implemented. Results: The findings reveal that the Sharia Restaurant in Egypt has implemented mudharabah contracts by the fatwas of the Egyptian Scholars Council, through profit-sharing mechanisms based on pre-agreed ratios (nisbah), transparent fund management, and active involvement of business partners in decision-making processes. These practices reflect the principles of justice, shared responsibility, and the avoidance of gharar (uncertainty) and riba (usury). Implications: The implications of this study highlight that adherence to local fatwas can serve as a strategic guide for strengthening Sharia-based microeconomics. For Islamic financial institutions and micro-entrepreneurs, this study offers insight and inspiration for implementing Sharia-compliant partnership-based contracts. Novelty: The novelty of this research lies in its focus on the local Egyptian context, which is rarely explored in the Sharia compliance literature, as well as its analytical approach to the implementation of local scholars’ fatwas in microeconomic practices.